IMPROVED DECOUPLING VIRTUAL SYNCHRONOUS GENERATOR CONTROL STRATEGY (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
The virtual synchronous generator (VSG) concept is one of the promising solutions to facilitate the integration of the renewable DG into microgrid. It consists in controlling the inverter-based DG to mimic synchronous machine characteristics leading to the grid stability improvement in case of high penetration level of renewable energy into the microgrid. The line impedance in low voltage and medium microgrids is present resistive or mixed resistive-inductive property. Therefore, the active and reactive powers are nonlinear functions and strongly coupled, which result in poor dynamic performance even instability of the DG based on conventional VSG control. To eliminate such coupling and enhance the stability and dynamic performance, a new decoupled VSG is proposed based on the injection of two additional control signals to the control variables in transit steady state, the expression of the control signals is obtained by applying a small signal approach. The proposed VSG control has been implemented and compared to conventional one using Matlab/Simulink. Simulation results show a significant improvement in the overshoot and setting time reduction 66.60 % and 99.55 %, respectively. Additionally, robustness results realized using a line parameters variation confirm the effectiveness of the proposed VSG control.
Keywords: Virtual synchronous generator; Vector synchronous generator (VSG); Microgrid; Renewable energy sources; Distributed generator; Grid stability